'Oh c'mon, those stories can't count in continuity!' Squirrel Girl and the problem of female power. Issue 1 (1st April 2014) - Goodrum, Michael
The history of superheroines is one of tensions, contradictions and difficulties. Squirrel Girl is no stranger to these, and her journey through the last twenty years of Marvel comic books has not been easy. In her debut in Marvel Super-Heroes #8 (S. Ditko and W. Murray, 1992), Squirrel Girl failed to become Iron Man's sidekick even though she saved him from Doctor Doom. Despite initial success, at least in terms of the narrative, Squirrel Girl disappeared for over ten years. When she reappeared in 2005, Squirrel Girl was in rather less illustrious surroundings – outside continuity. This article tracks the career of Squirrel Girl, focusing on strategies of narrative and visual representation and the relationship of the character to the structuring principle of continuity. Squirrel Girl demonstrates the ability to wield considerable power outside continuity but even here, where the victories of a woman can be easily disavowed thanks to their structural position within the Marvel universe, Squirrel Girl is still problematic. Various strategies of containment are implemented and this article will engage with these, demonstrating continuity and discontinuity in these policies as Squirrel Girl is ultimately drawn into continuity. Through a close critical reading of Squirrel Girl's appearances, then, this article will provide initial insights into how powerful women are simultaneously promoted and contained by superhero narratives.